Comparative evaluation of growth factors from platelet concentrates: An in vitro study - Anirban Chatterjee; Koel Debnath (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of the study was to compare and evaluate the various growth factors released for a period of 23 days from platelet rich fibrin (PRF) and platelet rich fibrin matrix (PRFM). Materials and Methods: A total of 15 systemically healthy controls were recruited and 10 ml of blood sample was withdrawn from the individual. Following the standard centrifugation protocol, PRF and PRFM were prepared. The platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), fibroblast growth factor (FGF), transforming growth factor (TGF), and insulin growth factor (IGF) were evaluated for 23 days. Results: The PDGF released from PRFM was statistically significant from PRF till the 15th day of release. The VEGF too had an increased release up till the 15th day from PRFM group as compared to PRF, but no statistically significant difference could be obtained. EGF from the 15th day to 23rd day had a greater release from PRFM group as compared to PRF group. FGF from 7th day to 23rd day had statistically significant difference in the PRFM group as compared to PRF group. TGF and IGF had statistically significant difference in PRFM group as compared to PRF group from 11th day to 23rd day and 1st to 17th day, respectively. Conclusion: The initial and robust release of GFs was seen in PRFM group at earlier days, whereas a steady and constant release of six GFs could be appreciated from PRF group upto 23rd day. Therefore, for a rapid and early healing and regeneration, both the platelet concentrates can be utilized in periodontal therapy.